Sustainability Standards and Global Governance 2020
DOI: 10.1007/978-981-15-3473-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Sustainability Standards and the Sustainable Development Goals

Abstract: Voluntary Sustainability Standards (VSS) have since long been used and referred to in the context of the evolving global sustainability and development agenda(s), such as the 1992 Rio Earth Summit's Agenda 21 or the United Nations Millennium Development Goals (MDGs) introduced in 2000. Discussions on the instrumental value of VSS in contributing to global development, however, have gained new ground since the adoption of the Sustainable Development Goals (SDGs) and 2030 Agenda for Sustainable Development in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Several certifications aim to promote social justice, improve respect for women's human rights, also seeking an impact on the Sustainable Development Goals (SDGs) and advancing in the fulfillment of their CSR agendas. In fact, it has been found that more and more VSS schemes and organizations refer to the SDGs in their official communications (Blankenbach, 2020) and that public sector carry out gender report to show their impact in SDG 5 (Cassano & Fornasari, 2022). Thus, the initiatives with a public origin especially are the ones that emphasize this purpose to a greater extent.…”
Section: Mission Motivation Justification or Drivers Of An Initiativementioning
confidence: 99%
“…Several certifications aim to promote social justice, improve respect for women's human rights, also seeking an impact on the Sustainable Development Goals (SDGs) and advancing in the fulfillment of their CSR agendas. In fact, it has been found that more and more VSS schemes and organizations refer to the SDGs in their official communications (Blankenbach, 2020) and that public sector carry out gender report to show their impact in SDG 5 (Cassano & Fornasari, 2022). Thus, the initiatives with a public origin especially are the ones that emphasize this purpose to a greater extent.…”
Section: Mission Motivation Justification or Drivers Of An Initiativementioning
confidence: 99%
“…In recent years, the number of certificates on the sustainability of economic activities, especially those related to the production and commerce of agri-food products is increasing due to the importance of the agricultural sector in the economy and which must continue to function constantly adapting to challenges (Blankenbach, 2020). The adoption of sustainable practices by Romanian agricultural companies is highlighted by the fact that they are voluntarily certified for international standards on sustainability, by this action being responsible for a development imperative to the agricultural sector, while ensuring transparency of the stages of the agri-food supply chain making available to consumers all the information that guarantees that the company has included in obtaining the product actions corresponding to the 3 pillars of sustainability: economic, social, environmental.…”
Section: Production and Consumption Trends To Achieve The Sustainable Development Goalsmentioning
confidence: 99%
“…One of the ways in which such global rulemaking has taken place is through voluntary sustainability standards (VSS) [11][12][13][14]. Different constellations of collaboration between public and private actors [12,15] have resulted in a multiplicity of VSS [16,17] addressing all kinds of sustainability issues along global value chains [18,19].…”
Section: Introductionmentioning
confidence: 99%